Effectiveness of direct patient outreach with a narrative naloxone and overdose prevention video to patients prescribed long-term opioid therapy in the USA: the Naloxone Navigator randomised clinical trial - Jason M Glanz; Ingrid A Binswanger; Shane R Mueller; Komal J Narwaney; Nicole M Wagner; Stanley Xu; Courtney R Kraus; Kris Wain; Sheila Botts (BMJ Public Health)
Introduction Public health efforts to reduce opioid overdose fatalities include educating people at risk and expanding access to naloxone, a medication that reverses opioid-induced respiratory depression. People receiving long-term opioid therapy (LTOT) are at increased risk for overdose, yet naloxone uptake in this population remains low. The objective of this study was to determine if a targeted, digital health intervention changed patient risk behaviour, increased naloxone uptake and increased knowledge about opioid overdose prevention and naloxone.Methods We conducted a pragmatic randomised clinical trial among patients prescribed LTOT in a healthcare delivery system in Colorado. Participants were randomly assigned to receive an animated overdose prevention and naloxone educational video (intervention arm) or usual care (control arm). The 6 min video was designed to educate patients about opioid overdose and naloxone, increase overdose risk perception and prompt them to purchase naloxone from the pharmacy. Over an 8-month follow-up, opioid risk behaviour was assessed with the Opioid-Related Behaviours in Treatment survey instrument, and overdose and naloxone knowledge was measured with the Prescription Opioid Overdose Knowledge Scale after viewing the video at baseline. Naloxone dispensations were evaluated using pharmacy data over a 12-month period. Data were analysed with generalised linear mixed effects and log-binomial regression models.Results There were 519 participants in the intervention arm and 485 participants in the usual care arm. Opioid risk behaviour did not differ between the study arms over time (study arm by time interaction p=0.93). There was no difference in naloxone uptake between the arms (risk ratio 1.13, 95% CI 0.77 to 1.66). Knowledge was significantly greater in the intervention arm compared with usual care (p<0.001).Conclusions A targeted, digital health intervention video effectively increased knowledge about opioid overdose and naloxone, without increasing opioid risk behaviour. Naloxone uptake did not differ between the intervention and usual care arms.Trial registration number NCT03337009.